Diversification of Tilapia into Frozen Food Products with Yellow Seasoning to Enhance the Activity and Economy - Arinta Kusumawardhani; Dynna Hidayah; Sam Tiara Puspa; Zahrani Putri Desta Sania; Ayu Anisa (Universitas Lambung Mangkurat, 2024)
Seventy percent of Indonesia's territory consists of water. Several regions make fish farming a livelihood to optimize this potential. One of them is Ponggok Village, Klaten. Ponggok Village already has superior products made from Nile tilapia fish, but product diversification is needed to expand market segmentation and increase income. By diversifying, products will be more interesting and varied and have a higher selling value. Nile tilapia fish can be converted into frozen food products with yellow spices through village community empowerment program training using the fourth step of the ABCD method, named the Asset Based Community Development method. The first step is to